Politeness Employed by Hermanto Tanoko in Hermanto Tanoko Podcast - Jessica Goldine; Nani Indrajani Tjitrakusuma (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This research examined Hermanto Tanoko's politeness while asking questions and using address terms to Tahir and Jehian Panangian Sijabat on his podcast. The writer also compared Hermanto Tanoko's  politeness to Jehian Panangian Sijabat and Tahir to find the similarities and differences. This research cites Watts (2003) for the politeness theory. Since politeness is cultural, the writer employed notions from Javanese culture by Suseno (2001). This qualitative research analyzed utterances made by Hermanto Tanoko. Hermanto Tanoko shows hormat (respect) by utilizing personal name, family term, or a combination of family term and personal name to address older people and using personal names to address younger people. Hermanto Tanoko used rukun (harmonious) while asking questions by hedging, being indirect, displaying attention or compassion, and joking. Despite their age gap, Hermanto Tanoko is polite to both guests which might happened due to the fact that Hermanto Tanoko is raised in the Indonesian (Javanese) culture.